1992
DOI: 10.1159/000292720
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Natural Killer Cell Activity in Women with Endometriosis

Abstract: Natural killer (NK) cell activity is characterized by the spontaneous capacity of lymphoid cells derived from nonimmunized hosts to recognize and lyse certain tumor cell lines, virus-infected cells and transplanted tumor cell lines. Endometriosis is characterized by implantation and proliferation of autologous ectopic tissue in the pelvic cavity. Therefore, we focused on examining NK cell activity in women with endometriosis. NK cell activity in peripheral blood from women with endometriosis was lower than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
8

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 12 publications
6
30
0
8
Order By: Relevance
“…In addition, we demonstrated that treatments with antide and TNF-SHARC increased NK cell activity similar to the human studies (Umesaki et al, 1999). Clinical data show reduced NK cell activity in women with endometriosis (Tanaka et al, 1992;Quaranta et al, 2006), which correlates with the severity of the disease (Wilson et al, 1994). Recent studies propose the decreased NK cell activity in women with endometriosis could be due to an increased proportion of NK cells expressing CD94/NKG2A (Galandrini et al, 2008).…”
Section: Discussionsupporting
confidence: 72%
“…In addition, we demonstrated that treatments with antide and TNF-SHARC increased NK cell activity similar to the human studies (Umesaki et al, 1999). Clinical data show reduced NK cell activity in women with endometriosis (Tanaka et al, 1992;Quaranta et al, 2006), which correlates with the severity of the disease (Wilson et al, 1994). Recent studies propose the decreased NK cell activity in women with endometriosis could be due to an increased proportion of NK cells expressing CD94/NKG2A (Galandrini et al, 2008).…”
Section: Discussionsupporting
confidence: 72%
“…The pathogenesis of endometriosis is not well understood. Several reports, Recombinant IL-2, U/ml We confirmed this defect, and with in vitro depletion of natural killer (NK) cells, using the anti-Leu-llb mono clonal antibody, we showed that NK cells were responsi ble for the in vitro killing of endometrial cells [2], Next, women with endometriosis had a decreased NK activity in peripheral blood [2], This was confirmed by several investigators [3][4][5][6],…”
Section: Introductionsupporting
confidence: 68%
“…The age range for the women with endometriosis was 22-39 years with a median o f 29.1, and for the women without endometrio sis it was 2 6 -4 4 years with a median o f 30. 4.…”
Section: Patientsmentioning
confidence: 99%
“…The pathogenesis of endometriosis, however, is also found to be associated with a derangement of the immune system, and especially with a decreased clearance of peritoneal fluid endometrial cells as a result of decreased cytotoxic T and natural killer (NK) cell activity. [2][3][4][5][6] A variety of inflammatory cytokines, such as interleukin-1, tumour necrosis factor-a, and interferon-c (IFN-c), have been reported to play important roles in endometriosis. [6][7][8][9] Among them, IFN-c is a multifunctional cytokine mainly secreted by T helper type-1 (Th1) cells and NK cells.…”
Section: Introductionmentioning
confidence: 99%